STUDY OF THE MICROBIOCENOTIC STRUCTURE AND OCCURRENCE FREQUENCY OF MICROORGANISMS ISOLATED FROM ANIMAL PRODUCTS IN THE WEST KAZAKHSTAN REGION - L. Dushayeva; A. Ichshanova; B. Yertleuova; D. Gabdullin; K. Murzabayev; A. Karagulov; R. Karmaliyev; A. Nametov; A. Tolegen (Animal Health and Biosafety, 2026)
The aim of this study was to determine the qualitative and quantitative composition of microorganisms isolated from food products of animal origin, to assess their frequency of occurrence, and to identify differences in microbial contamination depending on the type of food product. The study was conducted at the Veterinary and Biological Safety Research and Production Laboratory of the West Kazakhstan Agrarian-Technical University named after Zhangir Khan. A total of 175 samples of food products of animal origin were examined, including milk, minced meat, and animal by-products collected in the West Kazakhstan Region. Sampling and transportation were performed under aseptic conditions with compliance with sterility requirements and the cold chain. Microbiological investigations were carried out using conventional bacteriological methods and a range of general-purpose, selective, and differential diagnostic culture media. The isolated microorganisms were identified based on their morphological, tinctorial, and biochemical characteristics. Positive microbiological findings were obtained in 123 of the 175 examined samples, corresponding to 70.2% of the total sample set. Escherichia coli was the most frequently detected microorganism, being isolated from 53 samples (30.3%), followed by Staphylococcus spp. from 34 samples (19.4%), Enterococcus spp. from 17 samples (9.7%), and Bacillus from 12 samples (6.9%). Less frequently detected microorganisms included Rothia (1.7%), Corynebacterium (1.1%), and Gallibacterium (1.1%). The microbiocenotic structure was dominated by Enterobacteriaceae (43.1%) and Gram-positive cocci (41.5%), which together accounted for 84.6% of the identified microorganisms. Differences in the occurrence of microorganisms were observed among the examined food categories. The highest frequency of E. coli was recorded in animal by-products (26.8%), compared with 9.8% in milk and 6.5% in minced meat. Staphylococcus spp. were most frequently detected in milk (17.1%), whereas Enterococcus spp. and Bacillus were detected exclusively in animal by-products, at 13.8% and 9.8%, respectively. In addition, Corynebacterium, Rothia, and Gallibacterium were detected only in animal by-products. The obtained results demonstrate a considerable level of microbiological contamination of the investigated food products and considerable heterogeneity in their microbiocenotic structure. Animal by-products were characterized by the greatest diversity of isolated microorganisms and the highest overall frequency of their detection. The findings emphasize the importance of systematic veterinary-sanitary and microbiological monitoring of food products of animal origin and may serve as a basis for strengthening microbiological control measures in the West Kazakhstan Region.